REPRESENTASI RASA KEHILANGAN PADA IKLAN XL AXIATA VERSI “PESAN UNTUK RAKA” DI YOUTUBE (ANALISIS SEMIOTIKA ROLAND BARTHES PADA IKLAN YOUTUBE): (Analisis Semiotika Roland Barthes pada Iklan Youtube) - Laila Afrilia Riyadi; Ana Fitriana Poerana; Nurkinan (JURNAL KOMUNIKATIO, 2022)
Loss is a condition that anyone can experience. However, everyone has a different response depending on the loss experienced. The sense of loss as a state of reality in society is represented in communication media, one of which is advertising. This study aims to determine the representation of a sense of loss in the XL Axiata advertisement version of “Pesan untuk Raka” on youtube. Roland Barthes' semiotic approach examined signs of denotation, connotation, and formed myths. The focus of the study was the five stages of loss in the XL Axiata version of the “Pesan untuk Raka” advertisement. Research data was obtained from observations on advertisements. This study found seven scenes representing the five stages of loss in advertising. The results denoted that the impact of loss can be reduced by being together and caring for each other in the community. In conclusion, the elements of a sense of loss found in this study are denial, bargaining, depression, and acceptance.